Renal toxicity of therapeutic drugs. Issue 6 (27th May 2009) - John, R; Herzenberg, A M
Abstract : A number of therapeutic agents can adversely affect the kidney, resulting in tubulointerstitial, glomerular or vascular disease. Drug-induced tubulointerstitial nephritis and acute tubular necrosis are common, and are often cause by antibiotics or non-steroidal anti-inflammatory drugs. Drug-induced glomerular and vascular disease is relatively rare. This review describes the morphological patterns of drug-induced disease in the kidney. The histopathological changes are often similar to disease that is idiopathic or due to other causes, so that awareness and clinical correlation are most helpful to arrive at the aetiology.